Exploring the emotional effects of urban street design through virtual reality and electrodermal activity - Er, Ihsan Erdem; Heyik, Muhammet Ali; Yildirim, Ozge Ceylin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This study investigates how urban street design parameters influence physiological, emotional and perceptual responses using electrodermal activity (EDA) and self-report surveys in a virtual reality (VR) environment. Six street scenarios varying in sidewalk width, greenery, building height, land use and traffic were tested with 22 participants. Unlike prior VR-EDA research focused on extreme contrasts, this study includes moderate spatial variations to better capture environmental effects. Physiological data were collected using a low-cost Arduino-based GSR sensor, increasing methodological accessibility for planning and design contexts. The results indicate that wider sidewalks, greenery and pedestrian-oriented layouts are associated with lower stress, whereas narrow sidewalks, tall buildings and vehicular traffic correspond to higher stress levels. Although EDA and self-reports were not fully consistent across all scenarios, both measures differentiated low- and high-stress environments. The findings support the use of physiological indicators as quantifiable inputs for evidence-based street design and health-oriented urban planning.
Keywords: Environmental psychology; human-built environment interaction; street design parameters; electrodermal activity (EDA); virtual reality (VR); BUILT ENVIRONMENT; WALKING; STATE; Public Administration